Ion Channels in the Paraventricular Hypothalamic Nucleus (PVN); Emerging Diversity and Functional Roles - Feetham, Claire H. (Front Physiol, 2018)
The paraventricular nucleus of the hypothalamus (PVN) is critical for the regulation of homeostatic function. Although also important for endocrine regulation, it has been referred to as the “autonomic master controller.” The emerging consensus is that the PVN is a multifunctional nucleus, with autonomic roles including (but not limited to) coordination of cardiovascular, thermoregulatory, metabolic, circadian and stress responses. However, the cellular mechanisms underlying these multifunctional roles remain poorly understood. Neurones from the PVN project to and can alter the function of sympathetic control regions in the medulla and spinal cord. Dysfunction of sympathetic pre-autonomic neurones (typically hyperactivity) is linked to several diseases including hypertension and heart failure and targeting this region with specific pharmacological or biological agents is a promising area of medical research. However, to facilitate future medical exploitation of the PVN, more detailed models of its neuronal control are required; populated by a greater compliment of constituent ion channels. Whilst the cytoarchitecture, projections and neurotransmitters present in the PVN are reasonably well documented, there have been fewer studies on the expression and interplay of ion channels. In this review we bring together an up to date analysis of PVN ion channel studies and discuss how these channels may interact to control, in particular, the activity of the sympathetic system.